Head-shaking-induced nystagmus reflects dynamic vestibular compensation: A 2-year follow-up study - Striteska, Maja; Valis, Martin; Chrobok, Viktor; Profant, Oliver; Califano, Luigi; Syba, Jaroslav; Trnkova, Katerina; Kremlacek, Jan; Chovanec, Martin (Frontiers in Neurology, 2022)
Purpose We aimed to assess the ability of a head-shaking test (HST) to reflect vestibular compensation in patients after unilateral peripheral vestibular loss and to provide missing evidence and new insights into the features of head-shaking-induced nystagmus (HSN) over a 2-year follow-up. Background HSN may occur after a prolonged sinusoidal oscillation of the head. HSN is frequently observed in subjects with vestibular function asymmetry; it usually beats toward the functionally intact or “stronger” ear and can be followed by a reversal of its direction. Study design A prospective observational case-control study. Settings A tertiary academic referral center. Methods A total of 38 patients after acute unilateral vestibular loss (22 patients with vestibular neuronitis and 16 patients after vestibular neurectomy) and 28 healthy controls were followed for four consecutive visits over a 2-year period. A complex vestibular assessment was performed on all participants, which included spontaneous nystagmus (SPN), the caloric test, the head-shaking test (HST), the video head impulse test (vHIT), the Timed Up and Go (TUG) test, and the Dizziness Handicap Inventory (DHI) questionnaire. We established the criteria for the poorly compensated group to assess different compensatory behaviors and results. Results We found a time-related decrease in HSN (ρ < −0.84, p < 0.001) after unilateral vestibular loss. After 2 years of follow-up, HSN intensity in compensated patients reached the level of the control group; TUG and DHI also improved to normal; however, the caloric and vHIT tests remained abnormal throughout all follow-ups, indicating a chronic vestibular deficit. Besides, poorly compensated patients had a well-detectable HSN throughout all follow-ups; TUG remained abnormal, and DHI showed at least a moderate deficit. Conclusions Our study showed that, after a unilateral peripheral vestibular loss, the intensity of HSN decreased exponentially over time, reflecting an improvement in dynamic ability and self-perceived deficit. HSN tended to decline to the value of the control group once vestibular compensation was satisfactory and sufficient for a patient's everyday life. In contrast, well-detectable HSN in poorly compensated patients with insufficient clinical recovery confirmed the potential of HSN to reflect and distinguish between adequate and insufficient dynamic compensation. HSN could serve as an objective indicator of stable unilateral vestibular loss.